Down regulation of lactotransferrin enhanced radio-sensitivity of nasopharyngeal carcinoma. (February 2021) - Qi, Yi-Fan; Yang, Yang; Zhang, Yan; Liu, Shuzhen; Luo, Bing; Liu, Wen
Highlights: Patients with low LTF expression had a poor prognosis. LTF might interaction with DUSP1, PPARGC1A, FOS and SMARCA1. 42 target genes of miR-214 were cross-linked to radiotherapy sensitivity. Down regulation of lactotransferrin enhanced radio-sensitivity of nasopharyngeal carcinoma. Abstract: Introduction: It is reported that LTF had a radiation resistance effect, and its expression in nasopharyngeal carcinoma (NPC) was significantly down-regulated. However, the mechanism of down-regulated LTF affecting the sensitivity of radiotherapy has remained elusive. Methods: We re-analyzed the microarray data GSE36972 and GSE48503 to find differentially expressed genes (DEGs) in NPC cell line 5−8 F transfected with LTF or vector control, and the DEGs between radio-resistant and radio-sensitive NPC cell lines. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment and protein-protein interaction network (PPI) analysis of DEGs were performed to obtain the node genes. The target genes of miR-214 were also predicted to complement the mechanism associated with radiotherapy resistance because it could directly target LTF. Results: This study identified 1190 and 1279 DEGs, respectively. GO and KEGG analysis showed that apoptotic process and proliferation, PI3K-Akt signaling pathway were significantly enriched pathways. Four nodes (DUSP1, PPARGC1A, FOS and SMARCA1) associated with LTF were screened. And 42 target genes of miR-214 were cross-linked to radiotherapy sensitivity. Conclusions: The present study demonstrates the possible molecular mechanism that the down-regulated LTF enhances the radiosensitivity of NPC cells through interaction with DUSP1, PPARGC1A, FOS and SMARCA1, and miR-214 as its superior negative regulator may play a role in regulating the radiotherapy effect.